From land conflicts to the consolidation of lasting peace in Aboisso (south-eastern ivory coast) - Kouadio, Konan Leonard; Gohourou, Florent (Geografares, 2026)
Ivory Coast’s development is based on agriculture. This sector currently represents 22% of GDP, and more than two-thirds of the working population earn their living from farming. However, the challenges of agriculture face several problems, including the land issue. Nearly all regions of Côte d’Ivoire are affected by land conflicts (OASIS, 2017, p.12). This land situation is strongly marked by intense agrarian migration supported by the state since the 1960s. In the department of Aboisso, in the face of land conflicts, strategies are adopted for maintaining peace. This study therefore aims to understand, in the face of land conflicts, the strategies adopted for maintaining peace in Aboisso. Based on a mixed survey (qualitative and quantitative), it emerges that the absence of land titles, multiple sales of the same land and poor administrative management are the main causes of conflicts in Aboisso. The study also reveals that land conflicts in Aboisso pit indigenous peoples themselves against agricultural land exploitation rights, indigenous peoples against migrants, and village communities against large agro-industrial companies. Faced with these conflicts, victims resort to customary, judicial, and administrative settlement methods to consolidate peace in Aboisso.
Keywords: Aboisso; land conflicts; lasting peace; conflict resolution; Southeast